(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the effect of applying different concentrations of Epigallocatechin-3-gallate (ECGC) solutions at the resin/dentin interface. Healthy dentin surfaces were randomized into 4 groups (EGCG 2%; EGCG 6%, chlorhexidine and control). After application of the acid, EGCG was applied followed by the adhesive. A resin block was constructed and specimens with an adhesive interface were cut for microtensile mechanical testing and to obtain bond strength values ​​and fracture mode analysis, after 24h. Data were statistically analyzed by 1-way ANOVA and post Tuckey test with α = 5%. The results showed that the use of 2% and 6% EGCG increased the values ​​of adhesive strength at 24h, with no statistically significant difference between them, while the control and chlorhexidine groups differed from the first two, but had no difference between them. Thus, the application of EGCG at concentrations of 2% and 6%, as part of the adhesive restorative protocol, proved to be effective in increasing the bond strength after 24h of the restoration.